Model Pengelolaan Sumber Daya Mineral Berbasis Pemberdayaan Masyarakat menggunakan Inklusi Keuangan - Yoka Pramadi; Taufik Hidayat (Balitbangda Provinsi Lampung, 2018)
Indonesia has the potential mineral resources such as gold, silver, copper, nickel, tin, lead, aluminum, iron, manganese, chromite, petroleum, natural gas, coal, iodine, various salts, various industrial minerals (asbestos, bentonite, zeolite, sulfur, phosphate, limestone and others), precious stones including diamonds and building materials. Allegedly, potential mineral resources owned by Indonesia rank 6th in the world. Undeniably, mineral resources as one of the natural resource, a resource that is very important in supporting the Indonesian economy. Even some types of minerals, namely oil and gas, has become a cornerstone of the economy. However, mineral resources have not been managed for the maximum welfare of the people, especially the people around which is still classified as poor. After doing research, made mineral resource management model based on community empowerment through financial inclusion, namely training, provision of appropriate technology, Assistance, Post Management and Financing.